Green marketing in the airline industry in Europe - Fellingerová, Natália; San José Iglesias, Rafael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis analyses the elements of green marketing of airlines in Europe. It focuses on the consumers’ perceptions and attitudes toward green products or services from airlines and the factors influencing their decision to purchase these green services. A survey is conducted among 136 European respondents to assess the perceptions and attitudes of consumers in the airline industry. The results indicate that the higher price of green products of airlines is the most important negative factor, playing a role in the consumer decision making. Furthermore, weak brand association towards airlines offering green products as well as the lack of transparency are revealed in connection to green initiatives of airlines. Additionally, the middle-aged and middle-income consumers are revealed as target group of green services of the airlines. The thesis proposes recommendations to airlines offering green products and services about the clarity of their green advertisements and rewards to consumers for purchasing the green products and services. Lastly, some limitations of the research are explained.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses